Immunomodulatory nanomedicine for colorectal cancer treatment: a landscape to be explored?. (1st April 2021) - Silveira, Maria José; Castro, Flávia; Oliveira, Maria José; Sarmento, Bruno
Abstract : Immunomodulatory nanomedicine has the potential to modulate CRC tumors with distinct associated immune cells,  leading to the recruitment and activation of the immune populations, which will further, recognize tumor cells and allow its elimination. Abstract : Colorectal cancer (CRC) is one of the deadliest cancers in the world mainly due to metastasis events. Despite improvements, the available treatment modalities for metastatic cases are limited, being generally associated with poor prognosis. As is well known, the immunosuppressive tumor microenvironment (TME) plays a key role in tumorigenesis, promoting cancer cell immune escape and disease progression. In addition, accumulating evidence indicates that the immunosuppressive microenvironment is a critical barrier for antitumor immunity in CRC, being extremely important to modulate the immune microenvironment to inhibit the tumor-promoting immune response. Therefore, new and effective cancer immunotherapeutic approaches demand a better control over the TME to reverse these immunosuppressive conditions. According to the features of different nanomedicines, nanoparticles can constitute a promising strategy, using different materials with the inherent ability to modulate TME and also with the potential to target immunosuppressive cells, to deliver antigens or immunomodulatory agents to eliminate this tumor. In this review, we summarize the importance of the TME in the progression and treatment response of CRC, exploring the potential of the nanotechnology for the development of immunomodulatory therapeutic strategies.